(untitled) - Atkinson, Paul (Indianapolis, IN, 2012)
Get up to speed on the extensive changes to the newest release of Microsoft SQL Server The 2012 release of Microsoft SQL Server changes how you develop applications for SQL Server
Keywords: Máy chủ / khách,Database management,Quản lý cơ sở dữ liệu; Client/server computing